Allergic respiratory diseases in the elderly - Todo-Bom, A (2010)
In industrialized countries there has been a significant increase in life expectancy, but chronic diseases are still important causes of death and disability in the elderly. Individuals over 65 years of age have a decrease in organic functions and lungs can lose more than 40% of their capacity. Although asthma and allergic rhinitis are more common in young people their prevalence in the elderly is increasing and the mortality reported in these patients is high. Asthmatic airways show an accumulation of activated eosinophils and lymphocytes determining structural changes of the bronchi. Local allergic inflammation, changes in T cell phenotypes and in apoptosis contribute to systemic inflammation. An increased risk of respiratory infections and neoplasic diseases has been recognized. These patients have increased susceptibility to atherosclerosis and cardiovascular diseases. Metabolic diseases are associated with an impairment of lung function and with systemic inflammation. Summing up older asthmatic patients have an increased risk to premature disability and death. A proper therapeutic approach to asthma can minimize this evolution. To identify the triggers is an important goal that allows reducing medication needs. Corticosteroids dampen allergic inflammation; therefore, they are the first choice in the treatment of patients with persistent asthma and rhinitis. Second-generation H1 receptor antagonists have reduced side effects and can be used if necessary. The elderly may have difficult access to health care. They should be educated about their disease and receive a written treatment plan. This information improves the quality of life, socialization and disease outcome in older people.